2014
DOI: 10.1111/labr.12027
|View full text |Cite
|
Sign up to set email alerts
|

Internet‐Based Employer Search and Vacancy Duration: Evidence from Finland

Abstract: This study investigates the effect of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…A study conducted in Finland found that the introduction of the web-based service shortened the average duration of vacancies in some regions but not in others. In addition, employers in urban areas were more likely to benefit from the introduction of online service [63].…”
Section: A Comparison Of Personnel Recruitment Behaviors In Italian Mmentioning
confidence: 99%
“…A study conducted in Finland found that the introduction of the web-based service shortened the average duration of vacancies in some regions but not in others. In addition, employers in urban areas were more likely to benefit from the introduction of online service [63].…”
Section: A Comparison Of Personnel Recruitment Behaviors In Italian Mmentioning
confidence: 99%